Randomised, controlled, double‐blind study of combination therapy of oral tranexamic acid and topical hydroquinone in the treatment of melasma. (28th February 2020) - Shihab, Nahla; Prihartono, Joedo; Tovar‐Garza, Andrea; Agustin, Triana; Legiawati, Lili; Pandya, Amit G
Abstract: Background/Objectives: Melasma is a common pigmentary disorder for which oral tranexamic acid has shown some efficacy in previous studies. The aim of this study was to assess the effectiveness of oral tranexamic acid in combination with hydroquinone cream in the treatment of melasma. Methods: Subjects with moderate‐to‐severe melasma were enrolled. Group A received hydroquinone 4% cream, sunscreen and oral tranexamic acid, while Group B received hydroquinone 4% cream, sunscreen and placebo capsules for 3 months. All subjects had an additional 3‐month follow‐up visit on sunscreen alone. The primary outcome measure was change in modified Melasma Area and Severity Index (mMASI) score. In addition, the melanin index was measured using a mexameter. Results: Fifty subjects were enrolled, and all completed the study. There was a 55% reduction in mMASI after 3 months from mean 8.96 (SD 2.45) to 4.0 (SD 1.6) in Group A compared to 10.9% from mean 8.53 (SD 2.04) to 7.6 (SD 2.0) in Group B. Three months after oral and topical therapy was discontinued, there was a 42% decrease in mMASI compared to baseline in Group A (mean 5.1 SD 1.7) vs. 4.7% in Group B (mean 8.1 SD 2.0). No serious adverse events were observed. Conclusions: A combination of oral tranexamic acid and topical hydroquinone is more effective than hydroquinone alone in the treatment of melasma.